Computer technology and Its Application in statistical measurement of college English education - Longmei Gu (Systems and Soft Computing, 2025)
While meeting the new environment and opportunity of the computer network environment, traditional English teaching also faces infinite impacts and challenges. How to guide the two to efficiently integrate resources has become an important issue to promote the transition from traditional to modern college English teaching in my country. When it comes to educational statistical measurement, which is one of three key disciplines of educational scientific study in the world today, it has wide practical significance in the process of education and teaching. Therefore, this paper has completed the following tasks: 1) A comprehensive review of the research results of English teaching mode in the computer network environment and educational statistics measurement to guide foreign language teaching practice at home and abroad. 2) Introduce the basic principle of RBF neural network and build a diversified English teaching quality evaluation index system. 3) Using a trained RBF model, input the data, then compare the output results with the expert evaluations. The results of the tests reveal that the model performs better than the competition.